Interference Management in Massive MIMO HetNets: A Nested Array Approach - Feng, Mingjie; Mao, Shiwen (arXiv.org, 2016)
The nested array, which is implemented by nonuniform antenna placement, is an effective approach to achieve O(N^2) degrees of freedom (DoF) with an antenna array of N antennas. Such DoF refers to the number of directions of incoming signals that can be resolved. With the increased number of DoF, an important application of nested array is to nullify the interference signals from multiple directions. In this paper, we apply nested array in a massive MIMO heterogeneous network (HetNet) for interference management. With nested array based interference nulling, each base station (BS) can nullify a certain number of interference signals. A key design issue is to select the interference sources to be nullified at each BS. We formulate this problem as an integer programming problem. The objective is to maximize the sum rate of all users, subject to BS DoF constraints. We propose an approximation scheme to solve this problem and derive a performance upper bound. Simulation results show that the proposed scheme effectively improves the sum rate and achieves a near optimal performance.